2006
DOI: 10.1111/j.1468-1293.2006.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term assessment of nevirapine‐containing highly active antiretroviral therapy in antiretroviral‐naive HIV‐infected patients: 3‐year follow‐up of the VIRGO study

Abstract: ObjectivesData on the durability of antiretroviral regimens over a 3-year period have only rarely been reported. The aim of this study was to evaluate the long-term efficacy and safety of one or two daily doses of nevirapine (NVP), in combination with stavudine (d4T) and didanosine (ddI), in HIV-infected patients. MethodsThis study was a follow-up of the VIR (amune) Grand Ouest (VIRGO) study, a 12-month open-label trial to assess the safety and immunovirological activity of NVP-d4T-ddI combination therapy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Longterm safety was very satisfactory, with no unexpected toxicities. The global percentage of withdrawals due to adverse effects through 36 months is similar to that reported in other studies of combinations of EFV and another backbone, 1,3,5,6 and it was also similar to that in the 5-year follow-up study with 3TC-stavudine (d4T)-lopinavir/ritonavir reported by Abbott. 7 Concerning hepatotoxicity, four cases were seen in the initial cohort 4 but during the extended study period no grade 3-4 hepatotoxicity was detected.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Longterm safety was very satisfactory, with no unexpected toxicities. The global percentage of withdrawals due to adverse effects through 36 months is similar to that reported in other studies of combinations of EFV and another backbone, 1,3,5,6 and it was also similar to that in the 5-year follow-up study with 3TC-stavudine (d4T)-lopinavir/ritonavir reported by Abbott. 7 Concerning hepatotoxicity, four cases were seen in the initial cohort 4 but during the extended study period no grade 3-4 hepatotoxicity was detected.…”
supporting
confidence: 86%
“…A SSESSMENTS OF DURABILITY of highly active antiretroviral therapy (HAART) and long-term safety have seldom been reported but are of major importance in order to select the best initial therapy. Among the nonnucleoside reverse transcriptase inhibitors (NNRTI), efavirenz (EFV) and nevirapine have been evaluated over a 2-to 3-year period in naive patients [1][2][3] but never in association with didanosine (ddI) and lamivudine (3TC). We present the 3-year follow-up results of an open-label, noncontrolled, observational, multicenter study of adult naive patients with HIV who started HAART with a once-daily regimen of ddI-3TC-EFV.…”
mentioning
confidence: 99%
“…However, NNRTIs are known for their potential to cause hepatotoxicity, which can lead to morbidity and therapy switches. Different studies have reported a cumulative incidence of severe hepatotoxicity varying from 1.4 to 15.6% in patients treated with NVP and from 1.1 to 10% in patients treated with EFV . However, the follow‐up time in these studies was relatively short, up to 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 2.9 million people in sub‐Saharan Africa and 0.6 million people in Asia were receiving antiretroviral therapy (ART) as of December 2008 [1]. More than 66% of ART regimens in these regions include the nonnucleoside reverse transcriptase inhibitor (NNRTI) nevirapine [1], which is highly effective [2], nonteratogenic [3,4] and has little long‐term toxicity [5,6]. Nevirapine, however, can cause early hepatotoxicity [7,8] and rash [9], including potentially life‐threatening hypersensitivity reactions [10].…”
Section: Introductionmentioning
confidence: 99%